Kutub al-Shaykh al-Sālimī wa-Mahārat al-Tawāṣul fīhā - Rawāḥī, Saʻīd ibn Aḥmad ibn Sayf (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
The book is the first teacher of the human being and its treasures are great and noble, above all the book that people love and cherish. Omanis found in the books of the learned Nūr al-Dīn Abū Muḥammad ʿAbd Allāh ibn Ḥumayd al-Sālimī what made them turn to them with strong attention: they printed them and brought them out in the finest form, established teaching circles for their study, and Omani houses came to hold at least one or two of his books. To understand the reasons for this requires a particular eye, a precise lens and a fresh idea, through which the skills of communication with others that gave his printed books their elevated standing among Omanis and others, and their lofty place among the books of the Islamic law, may be drawn out. In truth, diving into the content of his books to attain that end is like extracting the jewels of the sea: among his readers, one sought scholarly wealth and attained it.
MHF-PRINT2018-028
Keywords: ʿAbd Allāh al-Sālimī; Communication skills; Omani books; Reception of texts; Islamic scholarship; Reading culture